An analysis of the evidence underpinning the national comprehensive cancer network practice guidelines. (January 2022) - Love, Mitchell; Staggs, Jordan; Walters, Corbin; Wayant, Cole; Torgerson, Trevor; Hartwell, Micah; Anderson, J. Michael; Lillie, Anna; Myers, Kate; Brachtenbach, Travis; Derby, Micah; Vassar, Matt
Graphical abstract: Highlights: Used Systematic reviews in NCCN Detection, Prevention, and Risk Reduction guidelines. No high quality systematic reviews were found via the AMSTAR-2 assessment. Inconsistent adherence to PRISMA was found in included systematic reviews. Uncertain methodology underpinning NCCN guideline recommendations and evidence exists. Abstract: Objective: This study assesses the quality and completeness of systematic reviews (SRs) included by the National Comprehensive Cancer Network (NCCN) cancer screening clinical practice guidelines (CPGs). Methods: We evaluated SRs according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and AMSTAR-2 (A Measurement Tool to Assess systematic Reviews). Results: Seven NCCN CPGs were included with 109 SRs. The mean PRISMA percent completeness of included SRs was 71 % (range 0.1–1.0). The mean AMSTAR-2 percent completeness was 56 % (range 0.05−0.99). Of the 70 SRs assessed via AMSTAR-2, 42 (60 %) received a "critically low" rating, 11 (15.7 %) received "low" ratings, and 17 (24.3 %) received "moderate". None of the SRs received a "high" rating. Conclusion: Lack of adherence to AMSTAR-2 and PRISMA reporting standards among the SRs included is prevalent. We suggest improved reporting of SR inclusion criteria and evaluation to bolster the reporting quality of SRs underpinning CPG recommendations.